2000
DOI: 10.1177/089443930001800102
|View full text |Cite
|
Sign up to set email alerts
|

The Taxation of Internet Commerce

Abstract: The courts have found that Internet commerce is similar to interstate commerce in that it is largely exempt from taxation. Nonetheless, many state governments are attempting to tax the Internet broadly, levying transactions that would otherwise be considered nontaxable under the Commerce Clause of the U.S. Constitution and related interstate commerce statutes. This investigation assesses the current status of the taxation of Internet commerce and seeks to identify the factors that are associated with how state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Research design, has a great bearing on the reliability of the results arrived at and as such constitutes the firm foundation of the entire edifice of the research work. It helps the researcher to organise his or her ideas in a form whereby it will be possible to look for flaws and inadequacies (48). Research design is determined by the research purpose which could be explorative, descriptive, diagnostic or experimental in nature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research design, has a great bearing on the reliability of the results arrived at and as such constitutes the firm foundation of the entire edifice of the research work. It helps the researcher to organise his or her ideas in a form whereby it will be possible to look for flaws and inadequacies (48). Research design is determined by the research purpose which could be explorative, descriptive, diagnostic or experimental in nature.…”
Section: Methodsmentioning
confidence: 99%
“…Swahili word Harambee which means let's pull together was coined in the 1970s, and was popularised by Kenya's first president, Jomo Kenyatta, as a means of using community resources such as land, labour, and finance to establish training institutions mainly in rural areas (37). In as much as it was a development partnership slogan with a noble and successful idea, Harambee institutions mainly remained bottom ranking in the country.…”
Section: Status Of Media Training Colleges In Kenyamentioning
confidence: 99%
“…3. We compiled information on state Internet tax decisions from the Vertex TaxCybrary, the Commerce ClearingHouse State Tax Guide, and research by Dale Nesbary (2000).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the study by Best and Teske (2000) found that politics matter in taxing Internet sales. On the other hand, the study by Nesbary (2000) showed limited evidence that social and organizational factors influenced taxing e-commerce. The two empirical studies on the SSTP revealed that it will have some impact on firm's willingness to comply, and the economic and business environment had some bearing.…”
Section: Journal Of Internet Commercementioning
confidence: 92%
“…Nesbary (2000) tests a model examining the impact of taxation of goods and services sold over the Internet, taxation of Internet access fees, and taxation of digital downloads from the Internet. The findings reveal that only the application of a general sales tax was associated significantly with the application of Internet access.…”
Section: A Government's Perspectivementioning
confidence: 99%